Indonesia Development Policy Review : The Imperative for Reform - World Bank (Washington, DC, 2013)
Indonesia's recovery was already slowing several months before the events of September 11. Political instability had raised social tensions and slowed reforms--fueling capital flight, alarming investors, and delaying official external finance for development. Progress on bank restructuring had slowed and the debt of financially strapped corporations remained largely unresolved. Corruption flourished, unchecked by a justice system that itself was corroded. Regional tensions increased even as the country embarked upon an ambitious decentralization program. And, if real wages are any indication, progress on poverty reduction--encouraging in 1999 and 2000-ground to a halt. Although markets initially welcomed President Megawati Soekarnoputri into office, the new administration has made little progress on structural and governnance reforms in her first one hundred days in office, thus renewing nervousness in markets and worrying external donors and creditors. The events of September 11 have emphatically underscored the urgency of Indonesia's reform priorities. but donors need to be realistic about what is feasible, given strong vested interests, severe institutional weaknesses, the uncertainties arising from decentralization, and a turbulent transition to democracy. Progress is most needed in the key areas of structural reforms, good governance, and empowering and investing in the poor.